Nature-Young Adult Relationship in Anderson’s Speak: An Ecofeminist Reading - Thapa, Hukum (Bon Voyage, 2024)
This paper explores ecofeminism through a connection to the nature and a sexually assaulted young adult girl in Laurie Halse Anderson’s novel Speak. This study argues that adolescents suffer from the effects of rape. It also contends that aside from abusing teenagers, sexual assaulters also damage the victim’s ability to interact with the outside world. The rapists prevent the female protagonist from having healthy relationship with the nature. Therefore, it is crucial to re-establish connections with oneself, other people, and the natural environment in order to escape the horrible act of physical violation. For that purpose, this research paper employs the perspectives of Roberta S. Trites about young adults; and opinions of Carlos J. Adams and Greta Gaard about ecofeminism. In conclusion, this study hopes to pave the path for future research into the comprehensive interaction between a young adult’s (female) body and nature.